Store cattle prices, feeding strategies and the outlook for beef feedlots in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in Farm Management at Massey University - Gillingham, R. S. (Massey University, 1976)
An investment value model is fitted to data from the market for store cattle and a price expectations model developed for use by a prospective purchaser of steers. The model uses liveweight as the within-sales variable and responds to the major between-sales variables which are found to be ruling beef price, market mood, and climatic considerations. A computer model of the feeding and growth of a steer is constructed and used in conjunction with least-cost rations derived from a proxy schedule of feedstuff costs and qualities to identify feeding strategies which maximize the present nett discounted value of candidate steers. The conditions under which a prospective feedlot operator planning to make use of the optimal feeding strategy can expect the market price of candidate steers to fall below their nett present discounted value are found to include a product price advantage for the feedlot.
Keywords: Beef cattle; Cattle feed; Cattle prices